2005
DOI: 10.1097/01.ico.0000159730.45177.cd
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Penetrating Keratoplasty in Keratoconus

Abstract: Penetrating keratoplasty is a safe and effective procedure with remarkable optical and visual outcomes for patients with keratoconus who are contact lens intolerant or have unacceptable corrected visual acuity. Neither severity of the disorder nor trephination and suturing techniques significantly affects final visual outcomes. Less graft-recipient disparity (0.25 versus 0.50 mm) seems to induce less myopic shift.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
90
1
8

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(104 citation statements)
references
References 26 publications
5
90
1
8
Order By: Relevance
“…(14)(15)(16)(17)21,22) In a previous series of 90 consecutive PKPs performed in eyes with keratoconus and vernal keratoconjunctivitis between 1986 and 1996 in Saudi Arabia, 83 grafts (92.2%) were clear after a mean follow-up period of 44.7 months.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…(14)(15)(16)(17)21,22) In a previous series of 90 consecutive PKPs performed in eyes with keratoconus and vernal keratoconjunctivitis between 1986 and 1996 in Saudi Arabia, 83 grafts (92.2%) were clear after a mean follow-up period of 44.7 months.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Javadi et al, (16) the mean age at the time of surgery was 28.2 years, with 73.2% of patients being male. However, de Lavalette et al (17) reported a female predominance of 65% in their study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is a well-established procedure that provides satisfactory visual outcomes as evidenced by several studies (2,3) . However, in recent years, deep anterior lamellar keratoplasty (DALK) has been used as a safer alternative to PK.…”
Section: Introductionmentioning
confidence: 99%